Setting Standards in the West: C. B. Conway, Science, and School Reform in British Columbia, 1938–1974 - Fleming, Thomas; Conway, David (Canadian Journal of Education/Revue canadienne de l'éducation, 1996)
C. B. Conway headed the British Columbia Department of Education’s Division of Tests, Standards, and Research from the late 1930s to the mid-1970s. Through Conway and his research bureau, the department began to modernize its pedagogical foundations by embracing the scientific measurement movement that had been transforming education in the United States since the early 1900s. But more than this, Conway’s career provides a vantage point from which to see larger changes within educational government from the implementation of the so-called progressive reforms in the late 1930s, couched in ration- alism and science, to the neoprogressive reforms of the early 1970s, that were increasingly defined in political terms. C. B. Conway a dirigé la division des examens, des normes et de la recherche du mini- stère de l’Éducation de la Colombie-Britannique de la fin des années 30 au milieu des années 70. Grâce à M. Conway et à son bureau de recherche, le ministère a commencé à moderniser ses principes pédagogiques en adhérant au mouvement en faveur des mesures scientifiques, lequel transforme l’éducation aux États-Unis depuis le début des années 1990. La carrière de M. Conway constitue en outre un excellent filon pour analyser des changements plus vastes ayant trait aux politiques éducatives: de l’implan- tation, à la fin des années 30, des réformes dites progressives faisant appel au rationalisme et à la science jusqu’aux réformes néoprogressives du début des années 70, lesquelles ont été de plus en plus définies en termes politiques.